Tumor-associated macrophages in tumor progression and the role of traditional Chinese medicine in regulating TAMs to enhance antitumor effects - Zhang, Jiatong; Gao, Jiafeng; Cui, Jingwen; Wang, Yongqiang; Jin, Yipeng; Zhang, Di; Lin, Degui; Lin, Jiahao (Frontiers in Immunology, 2022)
Purpose: To emphasize the importance of tumor-associated macrophages (TAMs) in tumor immunity and to describe the ways in which extracts from Traditional Chinese Medicine (TCM) achieve tumor therapy by modulating macrophages. Significance: By summarizing these available data, this review focus on TAMs and TCM and can build the foundation for future research on antitumor therapeutics. Methods: In this review, we summarized the key functions of TAMs in cancer development and overviewed literature on TCM targeting TAMs together with other immune cells aiming to enhance antitumor immunity. Conclusions: With an indispensable role in antitumor immunity, TAMs contribute to tumor progression, migration, invasion, angiogenesis, lymphangiogenesis, and immunosuppressive microenvironment. In recent years, TCM has gradually gained attention as a potential antitumor adjunctive therapy in preclinical and clinical trials. TCM is also a regulator of cytokine secretion and cell surface molecule expression in balancing the tumor microenvironment (TME), especially macrophage activation and polarization. Therefore, it is believed that TCM could serve as the modifiers with the immunomodulatory capability.